Analisis Sektor Unggulan Daerah dalam Struktur Perekonomian Provinsi Sumatera Selatan - I Wayan Suparta; Sony Tian Dhora; Desi Wijayanti; Crisnina Handayani (CV. Syntax Corporation Indonesia, 2022)
The purpose of this study is to identify leading sectors that have comparative and competitive advantages in South Sumatra Province. The research method used is descriptive quantitative and the data used are sourced from the Central Statistics Agency (BPS) of South Sumatra Province. The data used include GRDP at constant prices for South Sumatra Province in 2017-2021. The analytical tools used are Static Location Quetiont (SLQ), Dynamic Location Quetiont (DLQ) and Shift-Share. The results of this research can be found in the quarrying and mining sector; agriculture, forestry and fishery sectors; water supply, waste treatment, waste and recycling sectors; the construction sector and the real estate sector are the leading sectors that meet the three analysis criteria above, which show positive numbers that have comparative and competitive advantages.